Visible-light-switched electron transfer over single porphyrin-metal atom center for highly selective electroreduction of carbon dioxide - Yang, Deren; Yu, Hongde; He, Ting; Zuo, Shouwei; Liu, Xiaozhi; Yang, Haozhou; Ni, Bing; Li, Haoyi; Gu, Lin; Wang, Dong; Wang, Xun (Nature communications, 2019)
External fields are introduced to catalytic processes to improve catalytic activities. The light field effect plays an important role in electrocatalytic processes, but is not fully understood. Here we report a series of photo-coupled electrocatalysts for CO 2 reduction by mimicking the structure of chlorophyll. The porphyrin-Au catalyst exhibits a high turnover frequency of 37,069 h −1 at −1.1 V and CO Faradaic efficiency (FE) of 94.2% at −0.9 V. Under visible light, the electrocatalyst reaches similar turnover frequency and FE with potential reduced by ~ 130 mV. Interestingly, the light-induced positive shifts of 20, 100, and 130 mV for porphyrin-Co, porphyrin-Cu, and porphyrin-Au electrocatalysts are consistent with their energy gaps of 0, 1.5, and 1.7 eV, respectively, suggesting the porphyrin not only serves as a ligand but also as a photoswitch to regulate electron transfer pathway to the metal center. The light field effect can improve performance in electrocatalytic processes, but is not fully understood. Here the authors design a photo-coupled electrocatalyst using a porphyrin ligand as a photosensitizer and a coordinated metal as a catalytically active site for carbon dioxide reduction.